Decoction and Fermentation of Selected Medicinal Herbs Promote Hair Regrowth by Inducing Hair Follicle Growth in Conjunction with Wnts Signaling. (24th March 2016) - Jang, Su Kil; Kim, Seung Tae; Lee, Do Ik; Park, Jun Sub; Jo, Bo Ram; Park, Jung Youl; Heo, Jong; Joo, Seong Soo
Abstract : It is well recognized that regulating the hair follicle cycle in association with Wnt signaling is one of the most interesting targets for promoting hair regrowth. In this study, we examined whether selected herbal medicines processed by decoction and fermentation promote hair growth by upregulating the number and size of hair follicles and Wnt signaling, including activation of β -catenin and Akt in telogen-synchronized C57BL/6N mice. The results revealed that the fermented extract after decoction (FDE) more effectively promoted hair growth than that of a nonfermented extract (DE). Notably, FDE effectively enhanced formation of hair follicles with clearer differentiation between the inner and outer root sheath, which is observed during the anagen phase. Mechanistic evidence was found for increased β -catenin and Akt phosphorylation levels in dorsal skin tissue along with elevated expression of hair regrowth-related genes, such as Wnt3/10a/10b, Lef1, and fibroblast growth factor 7. In conclusion, our findings suggest that FDE plays an important role in regulating the hair cycle by increasing expression of hair regrowth-related genes and activating downstream Wnt signaling targets.